Analisis Diskriminasi Pada Novel â€œAmeliaâ€ Karya Tere-Liye - Fheti Wulandari Lubis (Smart Education, 2018)
This study aims to describe the discrimination found in Tere-Liye's Amelia novel. To obtain the data used structural theory. The method used in this research is qualitative research method by way of descriptive analysis. The reason the authors use these methods because the authors attempt to describe the discrimination contained in the novel that became the object in this study. Data collection in this research is done by literature review technique and documentation technique. The author uses this documentation technique by reading the data source in the form of a novel with the purpose of identifying the data in accordance with the theory used. After obtaining research data, further analysis of research data is done by content analysis techniques. The process of data analysis is done by mastering and understanding the novel elements, identifying and analyzing discrimination. The results of data analysis show that there is discrimination contained in Tere-Liye's novel Amelia. the discrimination contained in the novel is the attitude of the community that does not allow the youngest child to go to school outside the region, the lack of freedom to express opinions, the youngest child in the family must stay and stay at home. Details of such discrimination have textual data that can prove the correctness of the analysis of the research data that can be proven. Keywords: discrimination, amelia, tere-liye